ANTI-HYPERCHOLESTEROLEMIA ACTIVITY OF ETHANOL EXTRACT Peperomia pellucid - Mazroatul, Chasanah; Deni, Glar Donia; Habibi, Nur Ahmad; Saputri, Gita Febri (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Hypercholesterolemia is a major cause of cardiovascular disease such as coronary heart disease. Betel water (Peperomia pellucida) is a type of plants that have antioxidant compounds that could delay, retard and prevent the oxidation of lipids, both enzymatic and non-enzymatic. This study aimed to determine the effect of ethanol extract Peperomia pellucida against total cholesterol, HDL, LDL, and triglycerides in the serum of white rats (Wistar) were given a diet aterogenetik, so it can be used as prevention of atherosclerosis. The active compounds contained in the water after screnning betel phytochemicals includes flavonoids, tannins, alkaloids, steroids and quinones. In vivo studies conducted by true experimental method with pre and post test with control group design. Rats were divided into 3 groups: group A positive control is given aterogenetik diet, group B and C were given diet Peperomia Pellucida aterogenetik and extract orally at a dose of 150 mg/kg and 300 mg/kg. Diet aterogenetik given as much as 20 grams per day for 14 days. Data obtained include total cholesterol, HDL, LDL, and triglycerides were analyzed by statistical methods Paired T Test oneway ANOVA (P < 0.05). The study of total cholesterol, HDL, LDL and triglycerides showed ethanol extract of Peperomia pellucida at a dose of 300 mg/kg body weight can lower total cholesterol and LDL significantly, but there was no significant decline in triglycerides and can increase HDL levels.